In Dora's case: Freud, hysteria, feminism - Bernheimer, Charles; Kahane, Claire (Columbia University Press, 1990)
A collection of essays that question Freud's assumptions about femininity and female desire. Several essays situate their critiques within the context of contemporary French writing on psychoanalysis and feminism, while others display the variety and finesse of the interpretive strategies exercised by contemporary feminist critics.
Keywords: approches et analyses; cours; discipline; fem1000; inégalités; premier cycle; psychanalyse; santé; santé des femmes*; sciences; sciences humaines; sexualité; systèmes d'oppressions; thématiques